PERCEPTIONS OF BETAWI ETHNIC PARENTS ABOUT GIRL HIGHER EDUCATION (STUDY IN BETAWI COMMUNITY IN SUDIMARA JAYA KELURAHAN, CILEDUG, TANGERANG) - Masruri, Ahmad (Khatulistiwa, 2024)
This article aims to reveal the Betawi community's perception of higher education in the Sudimara community. The research method used is qualitative with the interview method. This article focuses on the views of the Betawi community about highly educated women. Some of them parents want their daughters to have higher education in addition to careers and to educate their children. Some opinions from parents found from this study include realizing the importance of higher education for girls and some even requiring higher education.Keywords: Betawi community's perception, higher education, daughter